Association of Sex Hormones and Sex Hormone-Binding Globulin Levels With Bone Mineral Density in Adolescents Aged 12–19 Years - Xu, Ke; Fu, Yicheng; Cao, Buzi; Zhao, Mingyi (Frontiers in Endocrinology, 2022)
Background: Sex hormones are recognized to play a significant part in increasing BMD and promoting bone maturation during adolescence. The purpose of our study was to use a database with large population data to evaluate the association of bone mineral density with sex hormones (including testosterone and estradiol), and SHBG in adolescent boys and girls aged 12-19 years. Methods: Data for our study were taken from the National Health and Nutrition Examination Survey 2013-2016, and we used weighted multiple linear regression models to assess the relationship between testosterone, estradiol, and SHBG and total BMD. We use weighted generalized additive models and smooth curve fitting to discover underlying nonlinear relationships. Results: A total of 1648 teenagers (853 boys, 795 girls) were selected for the final analysis. In boys, testosterone, estradiol levels were positively associated with total BMD, whereas SHBG level was negatively associated with total BMD, after adjusting for covariates (P < 0.05; 95% confidence interval (CI)). In addition, there was a point between estradiol and total BMD after which the positive correlation between estradiol and total BMD was relatively insignificant in boys. In girls, there was a positive association between estradiol and total BMD (P < 0.05; 95% CI), but no significant association between the testosterone (β 0.0004; 95% CI -0.0001 to 0.0008), SHBG (β -0.0001; 95% CI -0.0002 to 0.0001) levels and total BMD. We also found an inverted U-shaped association between testosterone and total BMD with the inflection point at 25.4 ng/dL of testosterone. Conclusions: We found differences in the association of sex hormones with total BMD in boys and girls. Based on our findings, an appropriate increase in serum testosterone levels may be beneficial for skeletal development in girls, because of the inverted U-shaped relationship, high testosterone level might be detrimental to BMD. Furthermore, keeping estradiol levels below a certain level in boys (24.3 pg/mL) may be considered.